An application of q-Sumudu transform for fractional q-kinetic equation - UÇAR, FARUK (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2018)
The aim of this paper is to give an alternative solution for the q-kinetic equation involving the Riemann-Liouville fractional q-integral operator. The solution is obtained in terms of the q-Mittag-Leffler functions using inverse q-Sumudu transform. As applications, some corollaries are presented to illustrate the main results.
Keywords: Riemann-Liouville fractional q-integrals; q-kinetic equation; q-Sumudu transforms; REACTION-DIFFUSION EQUATIONS; Q-DERIVATIVES; Q-INTEGRALS